Analysis of Leading Sectors Potential for Economic Development Planning in Malang City - Rizani, Ahmad (Journal of Developing Economies, 2020)
This study aims to identify and determine the leading sectors in Malang City to illustrate leading economic activities that can be developed to boost economic potential in Malang City. The analysis tools used include Shift-Share, Location Quotient (LQ), and Growth Ratio Model (GRM) analysis. The results show that: (1) shift-share analysis showed that the economy of Malang City during the period 2010-2016 increased by Rp. 12,926,565.5 million. The increase in economic performance in Malang City can be seen from 16 (sixteen) sectors of economic activity that are positive; (2) Location Quotient (LQ) analysis showed the leading sectors in Malang City consisting of 7 (seven) sectors, i.e. water procurement, garbage, waste and recycling management, construction, retail and wholesale trade, car and motorcycle repair, financial and insurance services, education services, health services, and social activities and other services sector; (3) Growth Ratio Model (GRM) estimation showed that the dominant sectors of growth and large contributions consist of the retail and wholesale trade car and motorcycle repair, transportation and warehousing, accommodation and food provision, information and communication, financial and insurance services, real estate, education services and health services and social activities sectors; (4) weighting results based on Shift-Share, Location Quotient (LQ) analysis, and Growth Ratio Model (GRM) showed that five sectors based on the highest potential weighting results are the health services and social activities, education services, construction, retail and wholesale trade car and motorcycle repair, and financial and insurance services sector. Keywords: Economic Potential, Shift-Share, Location Quotient (LQ), Growth Ratio Model (GRM) JEL: R58;R11;O41